Towards Comparative Analysis of Resumption Techniques in ETL - Muddasir, Mohammed; K, Raghuveer; R, Dayanand (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2021)
Data warehouses are loaded with data from sources such as operational data bases. Failure of loading process or failure of any of the process such as extraction or transformation is expensive because of the non-availability of data for analysis. With the advent of e-commerce and many real time application analysis of data in real time becomes a norm and hence any misses while the data is being loaded into data warehouse needs to be handled in an efficient and optimized way. The techniques to handle failure of process to populate the data are very much important as the actual loading process. Alternative arrangement needs to be made for in case of failure so that processes of populating the data warehouse are done in time. This paper explores the various ways through which a failed process of populating the data warehouse could be resumed. Various resumption techniques are compared and a novel block based technique is proposed to improve one of the existing resumption techniques.